2021
DOI: 10.1186/s12887-021-03012-4
|View full text |Cite
|
Sign up to set email alerts
|

Developing practical clinical tools for predicting neonatal mortality at a neonatal intensive care unit in Tanzania

Abstract: Background Neonatal mortality remains high in Tanzania at approximately 20 deaths per 1000 live births. Low birthweight, prematurity, and asphyxia are associated with neonatal mortality; however, no studies have assessed the value of combining underlying conditions and vital signs to provide clinicians with early warning of infants at risk of mortality. The aim of this study was to identify risk factors (including vital signs) associated with neonatal mortality in the neonatal intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Thus far, a review that examined 84032 studies on prediction models concluded that only 5% had been externally validated [ 14 ]. Furthermore, current neonatal predictive models used in low resources settings are developed mainly for estimating in-hospital mortality [ 34 , 36 ]. The outcome of severely ill children is based on more than just in-hospital mortality as admission, readmission, and post-discharge mortality are intricately intertwined in impacting child survival.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, a review that examined 84032 studies on prediction models concluded that only 5% had been externally validated [ 14 ]. Furthermore, current neonatal predictive models used in low resources settings are developed mainly for estimating in-hospital mortality [ 34 , 36 ]. The outcome of severely ill children is based on more than just in-hospital mortality as admission, readmission, and post-discharge mortality are intricately intertwined in impacting child survival.…”
Section: Discussionmentioning
confidence: 99%
“…Kangaroo Mother Care is one prognostic determinant for preterm mortality. One reason is that KMC prevents hypothermia, which causes neonatal mortality (27,32). KMC offers many more benefits besides thermal protection, notably a successful initiation and maintenance of lactation and preventing apnea of prematurity.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-four (9.6%) preterm neonates had PNA. Seven percent (27) of the preterm neonates had hypoglycemia (Table 4).…”
Section: Immediate Morbidity Of Preterm Neonatesmentioning
confidence: 99%
“…The studies, as seen in Figure 2, include various technology interventions in NICU research: seven using Machine Learning (27)(28)(29)(30)(31)(32)(33), three combining Machine and Deep Learning (34)(35)(36), and fourteen exclusively focusing on Deep Learning (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Geographically, thirteen studies are from the USA (27,28,32,36,37,39,41,42,44,(46)(47)(48)(49), with others from Austria (two) (29,40), Taiwan (two) (43,45), and six in different countries including Argentina (31), China (35), Denmark (33), Iran (50), Italy (34), and Tanzania (30), along with one multinational dataset…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The 'Other' category spans a variety of outcomes, with different AI techniques employed. 'Mortality' is studied by four articles, mostly using Deep Learning (30,44,47,50). Lastly, 'Length of Stay' involves two studies, evenly split between Deep Learning and Machine Learning (27,45).…”
Section: Study Characteristicsmentioning
confidence: 99%